Exploring the Contribution of Teaching and Learning Processes in the Construction of Students’ Gender Identity in Early Year Classrooms - Amina Baig (Journal of Education and Educational Development, 2020)
The present study explores how gender identity construction takes place in a single gender classroom in early years. Qualitative research guided the study design which was conducted in two public sector single gender schools. The data were collected through observations of the teacher-student interaction, student-student interaction, focused group discussion, and semi-structured interviews. The study found that teaching and learning is gendered in single sex settings as gender messages are passed on to the students, who play an important role in the gender identity construction of these children. The study also indicated that the teachers’ personal experiences greatly affect their perceptions regarding gender identities. There was also evidence of teachers having different expectations for girls and boys. Schools were hence found promoting stereotypes regarding gender roles and responsibilities in a social context.
Keywords: Gender; Social theory; Classroom Interaction; Single sex